Developing a question prompt tool to prevent and manage early cardiovascular disease after hypertensive pregnancy: qualitative interviews with women and clinicians - Madeline Theodorlis; Jessica Edmonds; Sara Sino; Mavis S. Lyons; Jessica U. Ramlakhan; Kara Nerenberg; Anna R. Gagliardi (BMC Women's Health)
Abstract Background Persons (henceforth, women) who have hypertensive disorders of pregnancy (HDP) are at risk of premature cardiovascular disease (CVD). While largely preventable through lifestyle management, many women and clinicians are unaware of the risk. Based on prior research, we developed a question prompt tool (QPT) on preventing and managing CVD after HDP. The purpose of this study was to refine QPT design. Methods We recruited Canadian women who had HDP and clinicians who might care for them using multiple strategies, conducted telephone interviews with consenting participants, and used qualitative description and inductive content analysis to derive themes. Results We interviewed 21 women who varied in HDP type, CVD status, years since HDP pregnancy, age, geography and ethno-cultural group; and 21 clinicians who varied in specialty (midwife, nurse practitioner, family physician, internist, obstetrician, cardiologist), geography and years in practice. Participating women and clinicians agreed on needed improvements: more instructions, lay and gender-neutral language, links to additional information, more space for answers, graphic appeal, and both print and electronic format. Both groups identified similar barriers: clinicians lack time/willingness, and low language/health literacy and access to technology among women; enablers: translated, credible source/endorser, culturally relevant, organized by health trajectory stages; and likely benefits: raise awareness, empower women, encourage them to adopt healthy lifestyle. Women desired exposure to the QPT before or during pregnancy, while clinicians recommended waiting until postpartum to avoid overwhelming women. Similarly, most women said the QPT should be available through multiple avenues to empower them for health self-advocacy, while clinicians thought they should introduce the QPT to women, and decide when and which questions to address. To mitigate reluctance, clinicians recommended self-directed educational materials accompany the QPT. Conclusions We will use this information to refine QPT design and plan for future evaluation. If found to be effective and widely disseminated, the QPT could improve awareness and communication about this issue, and may reduce CVD risk in many women who have hypertensive pregnancies. Ongoing research is needed to more fully understand how QPTs support patient-clinician communication, and how to alert and prime both patients and clinicians to use QPTs.